Local anesthetic failure associated with inflammation: verification of the acidosis mechanism and the hypothetic participation of inflammatory peroxynitrite - Takahiro Ueno (Dove Medical Press, 2008)
Takahiro Ueno1, Hironori Tsuchiya2, Maki Mizogami1, Ko Takakura11Department of Anesthesiology, Asahi University School of Dentistry, Mizuho, Gifu, Japan; 2Department of Dental Basic Education, Asahi University School of Dentistry, Mizuho, Gifu, JapanAbstract: The presence of inflammation decreases local anesthetic efficacy, especially in dental anesthesia. Although inflammatory acidosis is most frequently cited as the cause of such clinical phenomena, this has not been experimentally proved. We verified the acidosis mechanism by studying the drug and membrane lipid interaction under acidic conditions together with proposing an alternative hypothesis. Liposomes and nerve cell model membranes consisting of phospholipids and cholesterol were treated at different pH with lidocaine, prilocaine and bupivacaine (0.05%–0.2%, w/v). Their membrane-interactive potencies were compared by the induced-changes in membrane fluidity. Local anesthetics fluidized phosphatidylcholine membranes with the potency being significantly lower at pH 6.4 than at pH 7.4 (p < 0.01), supporting the acidosis theory. However, they greatly fluidized nerve cell model membranes even at pH 6.4 corresponding to inflamed tissues, challenging the conventional mechanism. Local anesthetics acted on phosphatidylserine liposomes, as well as nerve cell model membranes, at pH 6.4 with almost the same potency as that at pH 7.4, but not on phosphatidylcholine, phosphatidylethanolamine and sphingomyelin liposomes. Since the positively charged anesthetic molecules are able to interact with nerve cell membranes by ion-paring with anionic components like phosphatidylserine, tissue acidosis is not essentially responsible for the local anesthetic failure associated with inflammation. The effects of local anesthetics on nerve cell model membranes were inhibited by treating with peroxynitrite (50 μM), suggesting that inflammatory cells producing peroxynitrite may affect local anesthesia.Keywords: inflammatory acidosis, local anesthetic failure, membrane lipid interaction, hypothetic mechanism, inflammatory peroxynitrite